Effects of stand structure and soil depth on soil properties in Cryptomeria japonica plantations - Luo, Laicong; Lin, Kang; Tao, Lingjian; Luo, Chao; Wang, Jianming; Duan, Tianze; Liu, Yubing; Fu, Xiaobin; Guo, Siqin; Liu, Yuanqiu (Frontiers in Forests and Global Change, 2025)
Stand structure plays a crucial role in forest management, directly influencing the physicochemical properties of forest soils and, consequently, forest health and productivity. Cryptomeria japonica plantations are widely distributed in the mountainous regions of Japan and China and hold an important ecological status. This study aims to investigate the effects of different stand structures and soil depths on the physicochemical properties of soils in Cryptomeria japonica plantations in the Lushan region of China. The study was conducted in the Lushan National Nature Reserve. Stand structure was classified into three categories—good, medium, and poor—based on canopy closure (<0.5, 0.5–0.7, >0.7), understory vegetation cover (>0.8, 0.6–0.8, <0.5), and stand density (<650, 650–900, >900 trees per hectare). Soil samples were collected from plots representing different stand structures at four depth intervals (0–10 cm, 10–20 cm, 20–30 cm, and 30–40 cm) and analyzed for soil bulk density, porosity, water-holding capacity, as well as for the contents of carbon (C), nitrogen (N), phosphorus (P), and their stoichiometric ratios. The results indicated that both stand structure and soil depth significantly affected the physical properties and stoichiometric characteristics of the soil. Compared with poor stand structures, good stand structures significantly reduced soil bulk density, increased porosity, and enhanced water-holding capacity. Moreover, soils in stands with good structure exhibited higher organic carbon and total nitrogen contents, particularly in the surface soil layer (0–10 cm), while the C:N, C:P, and N:P ratios gradually decreased with increasing soil depth. The study demonstrated that maintaining a good stand structure—characterized by low canopy closure, high understory vegetation cover, and moderate stand density—can significantly improve soil porosity, water-holding capacity, and nutrient cycling efficiency. These findings provide a scientific basis for sustainable forest management, suggesting that optimizing stand structure can enhance soil health and overall ecosystem functionality.